Exhaled nitric oxide predicts loss of asthma control in children after inhaled corticosteroids withdrawal. Issue 5 (27th January 2019) - Chang, Daniel V.; Teper, Alejandro; Balinotti, Juan; Castro Simonelli, Christian; Garcia‐Bournissen, Facundo; Kofman, Carlos
Abstract: Background: Exhaled nitric oxide (eNO) has been proposed for monitoring airway inflammation, diagnosis, and prediction of steroid responsiveness in asthma. However, its utility after elective suspension of asthma medication is still unclear. We aimed to determine the association between eNO values and the subsequent loss of asthma control (LAC) in asymptomatic asthmatic children after inhaled corticosteroids (ICS) withdrawal. Methods: We conducted a prospective observational cohort study. Forty‐two children (23 boys), mean age 11 years, with clinically controlled asthma, according to GINA guidelines, and receiving low‐dose of ICS (budesonide 200 μg/day or equivalent) were included immediately after the withdrawal of ICS. eNO, Asthma Control Test (ACT) and spirometry were monthly assessed, during 54 weeks or until the presence of at least one of the following criteria of LAC: 1) asthma exacerbation, 2) obstructive spirometric pattern, 3) ACT ≤ 19. Results: eNO baseline geometric mean (eNOb ), measured 4 weeks after discontinuation of ICS, was 23.7 ppb (SD: 1.16). An eNOb cutoff point of 21.8 ppb was determined to better discriminate between high and low eNO groups. Twenty‐five subjects (71.4%) had LAC. High eNOb was associated to LAC (OR: 9.01; 95CI: 1.10‐74.26). In addition, LAC occurred earlier in high eNOb than in low eNOb patients (8 vs 28 weeks, respectively; P = 0.017). Conclusions: Our findings suggest that eNO predicts loss of asthma control and may contribute for clinical follow up decisions during childhood asthma after ICS withdrawal.